Identification of Parasitoid Insects in the Coastal Area of Temboan Village in the Biological Control of the Coconut Pest Beetle Plesispa reichei Chapuis - Timpal, Tartius; Lepar, Meitha J.W; Mandagi, Conny M (Jurnal Ilmiah Sains, 2025)
This study aims to discover and identify types of parasitoid insects found in the coastal area of Temboan Village and examine their potential in biological population control of the pest Plesispa reichei. The research methodology consisted of four stages. 1) A preliminary survey, which included field observations of the physical characteristics of the study area, 2) Data collection for species identification, recording the number of species, and determining population size, 3) Data processing and analysis related to diversity and dominance, 4) The final stage involved drawing conclusions. This research reveals the presence of several species of parasitoid insects from the Chalcidoidea and Ichneumonoidea families, which exhibit high parasitism rates against this pest. The existence of these parasitoid insects suggests that biological control could be an effective strategy for managing the coconut plant ecosystem in the coastal area of Temboan Village. Apparently, this study identified only one type of pupal parasitoid, Tetrastichus brontispae on the coconut pest Plesispa reichei in the coastal area of Temboan and its surroundings. The high parasitism rate (50.5%) indicates that T. brontispae is highly effective as a biological control agent. This supports the use of parasitoids as a sustainable alternative for controlling Plesispa reichei populations. Keywords: Parasitoid Identification; Biological Control; Coconut Pest Beetle